Lansoprazole use and tuberculosis incidence in the United Kingdom Clinical Practice Research Datalink: A population based cohort. - Tom A Yates; Laurie A Tomlinson; Krishnan Bhaskaran; Sinead Langan; Sara Thomas; Liam Smeeth; Ian J Douglas (PLoS Medicine)
Background Recent in vitro and animal studies have found the proton pump inhibitor (PPI) lansoprazole to be highly active against Mycobacterium tuberculosis. Omeprazole and pantoprazole have no activity. There is no evidence that, in clinical practice, lansoprazole can treat or prevent incident tuberculosis (TB) disease. Methods and findings We studied a cohort of new users of lansoprazole, omeprazole, or pantoprazole from the United Kingdom Clinical Practice Research Datalink to determine whether lansoprazole users have a lower incidence of TB disease than omeprazole or pantoprazole users. Negative control outcomes of myocardial infarction (MI) and herpes zoster were also studied. Multivariable Cox proportional hazards regression was used to adjust for potential confounding by a wide range of factors. We identified 527,364 lansoprazole initiators and 923,500 omeprazole or pantoprazole initiators. Lansoprazole users had a lower rate of TB disease (n = 86; 10.0 cases per 100,000 person years; 95% confidence interval 8.1-12.4) than omeprazole or pantoprazole users (n = 193; 15.3 cases per 100,000 person years; 95% confidence interval 13.3-17.7), with an adjusted hazard ratio (HR) of 0.68 (0.52-0.89). No association was found with MI (adjusted HR 1.04; 95% confidence interval 1.00-1.08) or herpes zoster (adjusted HR 1.03; 95% confidence interval 1.00-1.06). Limitations of this study are that we could not determine whether TB disease was due to reactivation of latent infection or a result of recent transmission, nor could we determine whether lansoprazole would have a beneficial effect if given to people presenting with TB disease. Conclusions In this study, use of the commonly prescribed and cheaply available PPI lansoprazole was associated with reduced incidence of TB disease. Given the serious problem of drug resistance and the adverse side effect profiles of many TB drugs, further investigation of lansoprazole as a potential antituberculosis agent is warranted.